All Mixed Up: Making Sense of Mixed-Income Housing Developments. Issue 1 (2nd January 2017) - Vale, Lawrence J.; Shamsuddin, Shomon
Abstract : Problem, research strategy, and findings: Mixed-income housing is a popular strategy used by planners, developers, and government agencies to simultaneously revitalize blighted urban neighborhoods and preserve affordable housing for low-income residents. Yet the term "mixed income" is not consistently defined, so there is no clear understanding of what mixed-income housing is, what characterizes it, and how mixed-income projects differ from one another. Planners and policymakers are making important decisions about whether and how to pursue this urban redevelopment strategy without knowing the kinds of housing mixes available. We construct a data set of all 260 HOPE VI mixed-income redevelopment projects, analyze grant announcements, and obtain internal records from the U.S. Department of Housing and Urban Development. Using the data, we conduct a descriptive analysis of income mixes across projects. Based on this analysis and previous studies of income mixing, we develop a framework for categorizing key aspects of mixed-income housing. We identify four key dimensions for distinguishing current and future approaches to mixed-income housing: allocation, the proportion and range of incomes included in projects; proximity, the spatial scale at which income mixing is intended; tenure, the balance between rental housing and homeownership units; and duration, the amount of time projects remain mixed income based on funding restrictions. Planners can influence the nature of mixed-income housing projects by making choices about the range of options offered within these dimensions. We show that HOPE VI developments vary dramatically across all of them. We also highlight additional characteristics that may affect the broader community: rate of resident return, development size, building type, neighborhood characteristics, and race and ethnicity. Takeaway for practice: Planners need to understand the four dimensions to clarify the tradeoffs involved in decisions about mixed-income housing projects. Ultimately, this can help planners better design and plan projects that balance social goals and local conditions.